Discover the best answers at Westonci.ca, where experts share their insights and knowledge with you. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
To find the roots of the function [tex]\( f(x) = (x-6)^2 (x+2)^2 \)[/tex], we need to identify the values of [tex]\( x \)[/tex] that make the function equal to zero. Let's analyze the given function step-by-step.
1. Identify the factors of the function:
The function [tex]\( f(x) \)[/tex] can be expressed as the product of its factors:
[tex]\[ f(x) = (x-6)^2 (x+2)^2 \][/tex]
2. Find the values of [tex]\( x \)[/tex] that make each factor zero:
- For the factor [tex]\( (x-6)^2 \)[/tex]:
[tex]\[ (x-6)^2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x - 6 = 0 \implies x = 6 \][/tex]
The root here is [tex]\( x = 6 \)[/tex]. Since the factor [tex]\( (x-6) \)[/tex] is squared, the root [tex]\( x = 6 \)[/tex] has a multiplicity of 2.
- For the factor [tex]\( (x+2)^2 \)[/tex]:
[tex]\[ (x+2)^2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x + 2 = 0 \implies x = -2 \][/tex]
The root here is [tex]\( x = -2 \)[/tex]. Since the factor [tex]\( (x+2) \)[/tex] is squared, the root [tex]\( x = -2 \)[/tex] has a multiplicity of 2.
3. Summarize the roots and their multiplicities:
- The root [tex]\( x = 6 \)[/tex] has a multiplicity of 2.
- The root [tex]\( x = -2 \)[/tex] has a multiplicity of 2.
Therefore, the correct roots and their multiplicities are:
- [tex]\( -2 \)[/tex] with multiplicity 2
- [tex]\( 6 \)[/tex] with multiplicity 2
Hence, the answer is:
- [tex]\( -2 \)[/tex] with multiplicity 2
- [tex]\( 6 \)[/tex] with multiplicity 2
1. Identify the factors of the function:
The function [tex]\( f(x) \)[/tex] can be expressed as the product of its factors:
[tex]\[ f(x) = (x-6)^2 (x+2)^2 \][/tex]
2. Find the values of [tex]\( x \)[/tex] that make each factor zero:
- For the factor [tex]\( (x-6)^2 \)[/tex]:
[tex]\[ (x-6)^2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x - 6 = 0 \implies x = 6 \][/tex]
The root here is [tex]\( x = 6 \)[/tex]. Since the factor [tex]\( (x-6) \)[/tex] is squared, the root [tex]\( x = 6 \)[/tex] has a multiplicity of 2.
- For the factor [tex]\( (x+2)^2 \)[/tex]:
[tex]\[ (x+2)^2 = 0 \][/tex]
Solving for [tex]\( x \)[/tex]:
[tex]\[ x + 2 = 0 \implies x = -2 \][/tex]
The root here is [tex]\( x = -2 \)[/tex]. Since the factor [tex]\( (x+2) \)[/tex] is squared, the root [tex]\( x = -2 \)[/tex] has a multiplicity of 2.
3. Summarize the roots and their multiplicities:
- The root [tex]\( x = 6 \)[/tex] has a multiplicity of 2.
- The root [tex]\( x = -2 \)[/tex] has a multiplicity of 2.
Therefore, the correct roots and their multiplicities are:
- [tex]\( -2 \)[/tex] with multiplicity 2
- [tex]\( 6 \)[/tex] with multiplicity 2
Hence, the answer is:
- [tex]\( -2 \)[/tex] with multiplicity 2
- [tex]\( 6 \)[/tex] with multiplicity 2
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.